THE ROLE OF A BUSINESS PLAN IN THE MANAGEMENT OF AN ENTREPRENEURIAL STRUCTURE: KEY FUNCTIONS, TASKS AND CHARACTERISTICS OF DEVELOPMENT TO INCREASE COMPETITIVENESS - SALUN, Maryna; BASIURKINA, Nataliya; TARAN, Artem (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the significance of a business plan as the primary instrument for the administration of an entrepreneurial structure, guaranteeing competitiveness and stability in a dynamic market environment. Specific focus is given to the pivotal roles and responsibilities of business plans in the context of strategic planning, particularly in market analysis, identification of competitive advantages, and the formulation of marketing and financial strategies. The author identifies the principal elements of a business plan that directly influence the competitiveness of an enterprise structure in the market. These include the analysis of market trends, the forecasting of target audiences’ needs and the assessment of the competitive environment. Furthermore, the article underscores the significance of innovation and its influence on enhancing business efficiency, emphasizing the necessity of integrating contemporary technologies into business planning processes. It also examines the role of marketing strategy in developing a sustainable competitive advantage for an enterprise, including the selection of pricing strategies, sales channels, and communication channels with customers. Additionally, the article addresses risk management and human resources planning, which ensure an enterprise’s capacity to adapt to a dynamic environment. Thanks to effective management through a business plan, enterprises can form a strategy to ensure their sustainable growth in the face of dynamic market changes. In developing a business plan, it is vital to consider the innovative potential, pricing strategies and sales channels that allow for an effective position in the market. In further research, it is worth focusing on integrating the business plan with other management tools and studying the impact of corporate culture on the effectiveness of its implementation, which will allow creating a more adaptive and competitive enterprise management structure.